2011
DOI: 10.1007/s10067-011-1802-6
|View full text |Cite
|
Sign up to set email alerts
|

Gender-specific risk factors for incident gout: a prospective cohort study

Abstract: Previous reports suggested that gout incidence increased with serum uric acid (sUA) level. In addition to sUA, we aimed to examine the gender-specific risk factors for incident gout. A prospective study was conducted using data of the MJ Health Screening Center and outcome database from Taiwan's National Health Insurance. Cox proportional hazard model was used for risk analysis of incident gout. During a mean follow-up of 7.31 years for 132,556 individuals aged ≥18 years, 1,606 subjects (1,341 men and 265 wome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
82
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 84 publications
(89 citation statements)
references
References 18 publications
4
82
0
3
Order By: Relevance
“…Another similar study [3] looked at 233 asymptomatic hyperuricemic Taiwanese men followed for 5 years and confirmed that baseline level of uricemia was the main predictor of gout attacks. A more recent study [27] investigated a Taiwanese National Health Insurance database including 60 181 men and 72 375 women free from gout at baseline and followed-up for a mean of 7.31 years. In both sexes, the occurrence of gout increased with baseline uricemia.…”
Section: Hyperuricemia and Risk Of Gout Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Another similar study [3] looked at 233 asymptomatic hyperuricemic Taiwanese men followed for 5 years and confirmed that baseline level of uricemia was the main predictor of gout attacks. A more recent study [27] investigated a Taiwanese National Health Insurance database including 60 181 men and 72 375 women free from gout at baseline and followed-up for a mean of 7.31 years. In both sexes, the occurrence of gout increased with baseline uricemia.…”
Section: Hyperuricemia and Risk Of Gout Developmentmentioning
confidence: 99%
“…In some articles, the value at which the serum uric acid (SUA) is considered to become abnormal is lower in women than in men, but the retained sex-specific values differ across studies. Hyperuricemia was recently defined as above 7.7 mg/dl in men and above 6.6 mg/dl in women [27], or above 7.0 mg/dl in men and above 5.7 [28] or 6 mg/dl [29] in women. Many investigators defined increased SUA as above 7 mg/dl in men and above 6 mg/dl in women, in line with the recommendations of an epidemiology conference held in Rome in 1963 [30].…”
Section: Key Pointsmentioning
confidence: 99%
“…We recently reported the predictability of obesity and dyslipidemia for incident gout, which is more prominent in women than men (6). While a strong association between hyperuricemia and insulin resistance was shown (7,8), the combined effect between hyperuricemia and elements of metabolic syndrome on the development of gout was still uncertain.…”
Section: Introductionmentioning
confidence: 99%
“…Plusieurs études de suivi ont montré que le risque de goutte augmentait avec l'uricémie [11,[27][28][29][30][31]. Ces études ne se sont intéressées qu'aux gouttes avec manifestations cliniques et n'apportent pas de renseignement sur les dépôts asymptomatiques d'urate tels qu'on les a récem-ment observés en échographie [32].…”
Section: Uricémie Et Risque D'apparition De La Goutteunclassified
“…L'incidence de l'âge est confirmée par d'autres études. Les données de l'assurance maladie nationale de Taiwan, sur 60 181 hommes et 72 375 femmes sans goutte à l'inclusion ont été suivies pendant une moyenne de 7,31 ans [29]. Dans les 2 sexes, l'incidence de la goutte augmenta avec l'uricémie de départ, mais à uricémie égale, cette incidence augmentait aussi avec l'âge.…”
Section: Uricémie Et Risque D'apparition De La Goutteunclassified